CatIDS: Using market-based mechanism as a tool for protection by adaptation - Hassan, S.; Uddin, Md. Safi; Horani, S.; Abdelouahab, Abid (IEEE, 2005)
Market is an efficient adaptation tool that has been used since the beginning of humans' history to satisfy their ever-changing demands and supplies. In doing so, humans are able to adapt to whatever changes, and sustain their survivability. Realizing this fact, we argue that using market-based mechanism may make our computer security system better. Being one of the protection tools, Intrusion Detection System (IDS) may take the advantages of market-based mechanism to ensure that it always operates with minimum resources to achieve its purpose of detecting intruders and not interrupt users' important tasks. This IDS will adapt to network conditions to sustain its survivability.